Acral erosive mycosis fungoides: successful treatment with localised radiotherapy. (16th April 2013) - Wang, Connie Mengyan; Duvic, Madeleine; Dabaja, Bouthaina Shbib
Abstract : Mycosis fungoides encompasses a wide range of variants with differing clinical and histopathological findings, clinical courses and methods of treatment. Two patients were referred to MD Anderson Cancer Center for the evaluation of treatment-refractory palmoplantar dermatoses suggestive of a rare variant of mycosis fungoides—mycosis fungoides palmaris et plantaris (MFPP). Both patients eventually had progressive and ulcerative cutaneous disease extending beyond acral regions that showed remarkable response to local radiation therapy. Although most documented cases of MFPP show an indolent course, one must be aware of the possibility of development of severe cutaneous disease in patients initially presenting with palmoplantar involvement. Local radiotherapy is a safe and effective palliative treatment option for MFPP and cutaneous disease refractory to systemic treatment.